2019
DOI: 10.35940/ijitee.a4148.119119
|View full text |Cite
|
Sign up to set email alerts
|

Slope Stability of Landfill with Waste Degradation

Abstract: Nowadays, a large amount of municipal solid waste (MSW) is generated due to the rapid urbanisation in developing countries leads to the demand for larger and higher capacity landfills. Bioreactor landfill technology has been introduced to accelerate the stability of landfill and to solve the issue of limited landfill area. However, the accelerated degradation of the refuse in bioreactor landfills also considerably changes the geotechnical characteristics of the waste in the landfill and thereby increases the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furthermore, some fatalities in uncontrolled dumps occurred due to waste slides, which have caused major disasters worldwide [21,41]. The main causes leading to landfill slope instability are heavy rainfall that infiltrates waste, waste heterogeneity, waste with poor geotechnical features (in terms of shear strength, cohesion, and compressibility), and the lack of a waste compaction process [42,43].…”
Section: Effects Of Landfills On Public Health and Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some fatalities in uncontrolled dumps occurred due to waste slides, which have caused major disasters worldwide [21,41]. The main causes leading to landfill slope instability are heavy rainfall that infiltrates waste, waste heterogeneity, waste with poor geotechnical features (in terms of shear strength, cohesion, and compressibility), and the lack of a waste compaction process [42,43].…”
Section: Effects Of Landfills On Public Health and Environmentmentioning
confidence: 99%
“…Solid waste can also cause injuries due to the presence of sharp objects, while its surface can cause falls and could even collapse due to its poor geotechnical stability. Ismail et al [42] reported that surface deformations are caused by the low level of cohesion of solid waste and its friction angles. Accordingly, risks for workers, such as falling from height and cuts, should be considered together with falling objects/materials and entrapment due to the presence of sinking areas.…”
Section: Ohs Risk Assessmentmentioning
confidence: 99%
“…As reported by Ismail at al. (Ismail et al, 2019), inappropriate compaction rate of waste and its anaerobic degradation inside landfill cause high deformations due to low levels of cohesion and friction angle of solid waste, which impact on its shear strength. When there are not proper facilities to avoid collapse states, waste landslides can occur.…”
Section: On-site Hazards Identificationmentioning
confidence: 99%
“…Based on this, health and environmental problems related to illegal dumping and their management are deemed of major concern in most countries and a large number of studies addressing these issues can be found in literature (e.g. Porta et al, 2009, Ismail et al, 2019Jahanfar et al, 2017;Krook et al, 2012;Silvestri & Omri, 2008). Besides, some guidelines to carry out the cleanup of these sites (i.e.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%